Data popularity-based encrypted deduplication scheme without third-party servers - Guanxiong HA; Qiaowen JIA; Hang CHEN; Chunfu JIA (Tongxin xuebao)
It is effective to balance data security and storage efficiency for setting different levels of security protection for data based on popularity in encrypted deduplication systems.Existing schemes all need introduce a trusted third-party for recording data popularity, while the third party is prone to a single point of failure and efficiency bottleneck.To address this problem, a popularity-based encrypted deduplication scheme without third-party servers was proposed, which accurately recorded the data popularity based on the Count-Min sketch algorithm and Merkle Puzzles protocol, and achieved encrypted deduplication of unpopular data through the sPAKE protocols performed among users.Security analysis and experimental evaluation show that the proposed scheme is secure and efficient.